1978
DOI: 10.1007/bf00394300
|View full text |Cite
|
Sign up to set email alerts
|

Interstitial deletion of the long arm of chromosome 7 46,XX,del(7)(pter?q2200::q3200?qter)

Abstract: A newborn girl with multiple anomalies had an interstitial deletion of the long arm of chromosome 7 (46, XX,der(7)mat). The patient's mother and maternal grandmother were carriers of a balanced translocation, 46,XX, inv ins(5;7)(q14;q3200q2200). Both cytogenetic and clinical findings were similar to those in the two cases already described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

1984
1984
2002
2002

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 5 publications
1
20
0
Order By: Relevance
“…Of the 17 reported cases of interstitial 7q deletions, 6 lack bands 7qll-21 or q22 [Crawfurd et al, 1979;Gibson et al, 1982;Klep-de-Pater et al, 1979;Seabright and Lewis, 1978;Valentine and Sergovich, 19771, 7 are monosomic for regions 7q21 +q31 or q32 [Ayraud et al, 1976;Dennis et al, 1977;Franceschini et al, 1978;Higginson et al, 1978;Johnson et al, 1978;Klep-de-Pater et al, 1979;Serup, 19801, and 4 are missing segment 7q31-+q34 [Nielsen et al, 1979;Stallard and Juberg, 19811.…”
Section: Interstitial Deletionsmentioning
confidence: 98%
See 1 more Smart Citation
“…Of the 17 reported cases of interstitial 7q deletions, 6 lack bands 7qll-21 or q22 [Crawfurd et al, 1979;Gibson et al, 1982;Klep-de-Pater et al, 1979;Seabright and Lewis, 1978;Valentine and Sergovich, 19771, 7 are monosomic for regions 7q21 +q31 or q32 [Ayraud et al, 1976;Dennis et al, 1977;Franceschini et al, 1978;Higginson et al, 1978;Johnson et al, 1978;Klep-de-Pater et al, 1979;Serup, 19801, and 4 are missing segment 7q31-+q34 [Nielsen et al, 1979;Stallard and Juberg, 19811.…”
Section: Interstitial Deletionsmentioning
confidence: 98%
“…However, subsequent studies using R-and G-banding [de Grouchy et al, 19741 showed that the defect involved a nonreciprocal translocation from chromosome 6 to 7, effectively making the patient monosomic for the region distal to 7q32. Since that first report, another 32 cases of del (7q) have been described, including 15 terminal deletions [Bass et al, 1973;Bernstein et al, 1980;Biederman and Bowen, 1978;Francke, 1978;Friedrich et al, 1979;Harris et al, 1977;Kodama et al, 1980;Kousseff et al, 1977;Shokeir et al, 1973;Taysi et al, 1982;Turleau et al, 19791 and 17 interstitial deletions [Ayraud et al, 1976;Crawfurd et al, 1979;Dennis et al, 1977;Franceschini et al, 1978;Gibson et al, 1982;Higginson et al, 1976;Johnson et al, 1978;Klep-de-Pater et al, 1979;Nielsen et al, 1979;Seabright and Lewis, 1978;Serup, 1980;Stallard and Juberg, 1981;Valentine and Sergovich, 19771. Three patients with a ring 7 chromosome [Nakano and Miyamoto, 1977;Zackai and Breg, 19731 and one with a 7q terminal deletion associated with trisomy 9p [Turleau et al, 19741 have also been reported but are not included in our review of the dysmorphogenetic effects of del (7q) (Table I) because they are aneusomic for segments of the genome other than 7q and therefore do not represent pure 7q monosomy.…”
Section: Introductionmentioning
confidence: 97%
“…Seizures were described in 14 cases. No specific common region stood out; seizures were described in deletions of various sizes, extending from the pericentromeric region to the terminal region (91)(92)(93)(94)(95)(96)(97)(98)(99).…”
Section: Deletion Of the Long Arm Of Chromosomementioning
confidence: 99%
“…Seizure onset ranged from the neonatal period to 7 years (91,97). Febrile convulsions alone occurred in four cases (91,92,96,98), generalized seizures in three (94,95,97), myoclonic seizures in one (93), and a combination of afebrile and febrile seizures in one case (93). Two cases of Williams syndrome del(7)(q11.23), have been described with infantile spasms (100), but seizures are rare in this disorder.…”
Section: Deletion Of the Long Arm Of Chromosomementioning
confidence: 99%
“…The observation of three cases of ectrodactyly in proximal deletions 7q:7q11.2q22 [Pfeiffer, 1984; present case] and 7qllq21 or 22 [Del Porto et al, 19831 suggests a causal relationship, but more information is needed to confirm this. References Valentine and Sergovich, 1977Ayraud et al, 1976Higginson et al, 1976Dennis et al, 1977Franceschini et al, 1978Klep-de Pater et al, 1979Serup, 1980Abuelo and Padre-Mendoza, Young et al, 1984Martin-Pont et al, 1985Johnson et al, 1978Seabright and Lewis, 1978Klep-de Pater et al, 1979Crawfurd et al, 1979Gibson et al, 1982Del Porto et al, 1983Pfeiffer, 1984Young et al, 1984Fryns et al, 1985Frydman et al, 1986 …”
Section: Discussionmentioning
confidence: 98%